Attunement as a Pedagogical Starting Point - Andrew Foran (University of Alberta, 2021)
For many teachers, the value of pedagogical reflection is missing from practice. Rational educational approaches that prioritize judging and measuring students overshadow the relational dimension of teaching. Our study investigated this relational gap to explore more fully teachers’ attunement to the child as a unique person. We examined lived experiences of six teachers pedagogically engaged with children (K–12) participating in an active outdoor living program. The program aimed to develop a youth network of friends, nurturing positive self-esteem and youth leadership. Using a phenomenological method, we facilitated open-ended interviews to show teachers’ pedagogical awareness through hermeneutic conversations. We present the data as three anecdotes representing a synthesis of teacher reflection, writing, and on-going conversation. Our findings reveal the importance of being-in-time with children as teachers relate pedagogical moments with children learning outdoors. Through attunement as the flexibility to adapt educational challenges and approaches to suit the moment and uniqueness of the child, teachers became careful observers, allowing students to be children without the competing tensions of institutional expectations.